Two new empoascine leafhopper genera, Thaioasca and Mjolnirus, from Thailand (Hemiptera: Cicadellidae: Typhlocybinae), with a checklist of Empoascini in Thailand - Wang, Yi-Mei; Xu, Ye; Dmitriev, Dmitry A.; Dietrich, Christopher H.; Qin, Dao-Zheng (Zootaxa, 2021)
Two new microleafhopper genera of Empoascini, Thaioasca Wang, Xu & Qin, gen. nov. and Mjolnirus Wang, Xu & Qin, gen. nov., based on the type species, Thaioasca contaminata Wang, Xu & Qin, sp. nov. and Mjolnirus mediolobus Wang, Xu & Qin, sp. nov. are described from Thailand. Male habitus photos and illustrations of male genitalia of these two new species are given. A checklist of Empoascini from Thailand is also provided.